2017
DOI: 10.3847/1538-4357/aa937a
|View full text |Cite
|
Sign up to set email alerts
|

Interstellar Silicon Depletion and the Ultraviolet Extinction

Abstract: Spinning small silicate grains were recently invoked to account for the Galactic foreground anomalous microwave emission. These grains, if present, will absorb starlight in the far ultraviolet (UV). There is also renewed interest in attributing the enigmatic 2175Å interstellar extinction bump to small silicates. To probe the role of silicon in the UV extinction, we explore the relations between the amount of silicon required to be locked up in silicates [Si/H] dust and the 2175Å bump or the far-UV extinction r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
1

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 70 publications
(124 reference statements)
3
15
1
Order By: Relevance
“…Let a sil and a gra respectively be the mean sizes of the silicate and graphite grains, each weighted by grain area, grain mass, or V -band extinction cross section [C ext (a, λ V )]. We also derive the "overall mean grain size" as the average of a sil and a gra , weighted by the mass fraction of each dust component in the same manner as described in §6 of Mishra & Li (2017). Our results closely resemble that of Mishra & Li (2017;see their Figures 14, 15): the area-, mass-, and C ext (a, λ V )-weighted mean grain sizes all anti-correlate with R −1 V .…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Let a sil and a gra respectively be the mean sizes of the silicate and graphite grains, each weighted by grain area, grain mass, or V -band extinction cross section [C ext (a, λ V )]. We also derive the "overall mean grain size" as the average of a sil and a gra , weighted by the mass fraction of each dust component in the same manner as described in §6 of Mishra & Li (2017). Our results closely resemble that of Mishra & Li (2017;see their Figures 14, 15): the area-, mass-, and C ext (a, λ V )-weighted mean grain sizes all anti-correlate with R −1 V .…”
Section: Discussionsupporting
confidence: 59%
“…We also derive the "overall mean grain size" as the average of a sil and a gra , weighted by the mass fraction of each dust component in the same manner as described in §6 of Mishra & Li (2017). Our results closely resemble that of Mishra & Li (2017;see their Figures 14, 15): the area-, mass-, and C ext (a, λ V )-weighted mean grain sizes all anti-correlate with R −1 V . This clearly shows that denser regions of larger R V values, on an average, are characterized by larger grains.…”
Section: Discussionsupporting
confidence: 59%
“…From the observations of 16 Galactic sightlines, Haris et al (2016) claimed that that the silicon depletion correlates with the 2175 Å bump and the far-UV extinction rise. However, more recently Mishra & Li (2017) found that the bump strength correlates with carbon abundance instead of silicon and there is no correlation of far-UV extinction with either silicon or carbon abundance using a silicate-graphite model on a larger sample. This discrepancy could be related to the different methods adopted for determining the silicon dust depletion and usage of different interstellar abundances of silicon in the two studies.…”
Section: Introductionmentioning
confidence: 93%
“…Previously, extinction curve models suggested that small silicate grains are responsible for the far-UV rise (Mathis et al 1977;Draine & Lee 1984;Weingartner & Draine 2001;Clayton et al 2003). However, Mishra & Li (2017) fitted the observed Galactic sightlines with a silicate-graphite dust model and reported that neither silicate nor carbonaceous dust correlates with the far-UV extinction. The far-UV extinction may therefore originate from a combined effect of both small carbon and silicate grains.…”
Section: Far-uv Rise Against Dust-phase Si and Fementioning
confidence: 99%
“…The discrepancy between the lower estimates of total carbon abundances and dust models is known as the "carbon crisis" (Kim & Martin 1996). However, the models based on UV extinction curves only indirectly estimate the amount of carbon in the solid phase (Mishra & Li 2017). A direct spectroscopic measurement is desirable.…”
Section: Introductionmentioning
confidence: 99%